2018
DOI: 10.1074/jbc.ra118.002787
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β fibrils assembled on ganglioside-enriched membranes contain both parallel β-sheets and turns

Abstract: Some protein and peptide aggregates, such as those of amyloid-β protein (Aβ), are neurotoxic and have been implicated in several neurodegenerative diseases. Aβ accumulates at nanoclusters enriched in neuronal lipids called gangliosides in the presynaptic neuronal membrane, and the resulting oligomeric and/or fibrous forms accelerate the development of Alzheimer's disease. Although the presence of Aβ deposits at such nanoclusters is known, the mechanism of their assembly and the relationship between Aβ secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 55 publications
(77 reference statements)
1
57
0
Order By: Relevance
“…In one study, using ganglioside-enriched, planar bilayers, (20:40:40 monolayers of GM1, SM, and cholesterol on POPC-coated mica), AFM showed fibril formation, and FTIR reflection-absorption spectroscopy suggested parallel β-sheet structure. 105 Fibrils formed in the absence of these lipids had FTIR spectra suggestive of antiparallel β-sheet structure, though these results need to be interpreted cautiously, because FTIR has previously suggested antiparallel β-sheet structure when higher resolution and more detailed solid-state NMR ultimately proved parallel β-sheet structure. 109 An important remaining question in these studies is the nature of the interaction between Aβ peptide and gangliosides such as GM 1 .…”
Section: The Role Of Gangliosides In Combination With Cholesterolmentioning
confidence: 96%
See 1 more Smart Citation
“…In one study, using ganglioside-enriched, planar bilayers, (20:40:40 monolayers of GM1, SM, and cholesterol on POPC-coated mica), AFM showed fibril formation, and FTIR reflection-absorption spectroscopy suggested parallel β-sheet structure. 105 Fibrils formed in the absence of these lipids had FTIR spectra suggestive of antiparallel β-sheet structure, though these results need to be interpreted cautiously, because FTIR has previously suggested antiparallel β-sheet structure when higher resolution and more detailed solid-state NMR ultimately proved parallel β-sheet structure. 109 An important remaining question in these studies is the nature of the interaction between Aβ peptide and gangliosides such as GM 1 .…”
Section: The Role Of Gangliosides In Combination With Cholesterolmentioning
confidence: 96%
“…There have been only limited studies on the structure of fibrils formed on a ganglioside substratum, but most of these suggest that the fibrils thus formed have the parallel, in‐register β‐sheet structure of most mature amyloid fibrils. In one study, using ganglioside‐enriched, planar bilayers, (20:40:40 monolayers of GM1, SM, and cholesterol on POPC‐coated mica), AFM showed fibril formation, and FTIR reflection–absorption spectroscopy suggested parallel β‐sheet structure . Fibrils formed in the absence of these lipids had FTIR spectra suggestive of antiparallel β‐sheet structure, though these results need to be interpreted cautiously, because FTIR has previously suggested antiparallel β‐sheet structure when higher resolution and more detailed solid‐state NMR ultimately proved parallel β‐sheet structure …”
Section: The Role Of Gangliosides In Combination With Cholesterolmentioning
confidence: 99%
“…A-beta accumulations have also been noted to occur in ganglioside-rich regions of the presynaptic terminal (Yamamoto et al, 2008) (see also figure 1), and can tightly bind to GM1 ganglioside (Yanagisawa et al, 1995). These interactions can induce the seeding of a-beta aggregates with fibrillar morphologies and beta-sheet structures (Matsubara et al, 2018;Yanagisawa, 2007). GM1 ganglioside may play a role in the pathogenesis of Alzheimer's disease through these mechanisms, and some studies have shown that a-beta accumulates in GM1 postmortem brain (Keilani et al, 2012).…”
Section: Ivb: Gm1 Gangliosidosismentioning
confidence: 95%
“…Oligomeric Aβ peptides aggregate around lipid rafts embedded in neuronal cell membranes. Recently, it has been shown that GM1 interacts with Aβ peptides, which induces self-assembly of β-sheets leading to polymerization, formation of fibrils and ultimately neurodegeneration [146]. This may be problematic as polymerization of Aβ fibrils may disrupt extracellular trafficking and communication between cells.…”
Section: Alzheimer's Diseasementioning
confidence: 99%